2008
DOI: 10.2147/cia.s3551
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between myocardial enzyme serum levels and markers of inflammation with severity of coronary artery disease and Gensini score: A hospital-based, prospective study in Greek patients

Abstract: Background: Our objective was to associate serum levels of myocardial enzymes and infl ammatory biomarkers with severity of coronary artery disease (CAD). Patients and methods: 123 patients participated in our study, including 65 cases of acute myocardial infarction (MI), 27 cases of newly diagnosed CAD -without MI -and 31 controls. In all subjects, myocardial serum enzyme levels (creatine phosphokinase, aspartate aminotransferase, lactate dehydrogenase) and infl ammatory indices (C-reactive protein, fi brinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 62 publications
3
25
0
1
Order By: Relevance
“…Patients with MVD presented a higher Gensini score among the 3 groups (non-CAD, 6.0 (Figure 2A). Although no significant differences were seen among the 3 groups in terms of peripheral total monocyte counts, CD14 + CD16 + monocyte counts were significantly higher in patients with MVD (84 [58-120] cells/μl) than in those with SVD (vs. 47 cells/μl, P<0.001) or without CAD (vs. 28 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] cells/μl, P<0.001) (Figure 2B). However, CD14 + CD16 − monocyte counts were not significantly different among the 3 groups.…”
Section: Patients' Characteristicsmentioning
confidence: 96%
“…Patients with MVD presented a higher Gensini score among the 3 groups (non-CAD, 6.0 (Figure 2A). Although no significant differences were seen among the 3 groups in terms of peripheral total monocyte counts, CD14 + CD16 + monocyte counts were significantly higher in patients with MVD (84 [58-120] cells/μl) than in those with SVD (vs. 47 cells/μl, P<0.001) or without CAD (vs. 28 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] cells/μl, P<0.001) (Figure 2B). However, CD14 + CD16 − monocyte counts were not significantly different among the 3 groups.…”
Section: Patients' Characteristicsmentioning
confidence: 96%
“…23 In the current study, serum levels of LDH and AST were significantly increased in MI. Peppes et al 24 have…”
Section: Discussionmentioning
confidence: 96%
“…In this regard Peppes et al (2008) [31] stated that cardiac troponin is the gold standard in the diagnosis of acute coronary syndrome and is measured in all patients with symptoms suggestive of acute coronary syndrome, in conjunction with physical examination and ECG. On the other hand, Antman (2008) [29] and Apple (2010) [32] reported that some patients with myocardial infarction in his study did not have elevated troponins or CK values and they may die before the cardiac markers reach the threshold.…”
Section: Discussionmentioning
confidence: 99%